Recruitment Methods in the Information Technology Rural Librarian Master’s Scholarship Program (Part I and Part II): Implications of Social Justice in the Southern and Central Appalachian Region - Mehra, Bharat; Singh, Vandana (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
The Information Technology Rural Librarian Master’s Scholarship Program Part I (ITRL) and Part II (ITRL2) are two grant projects funded by the Institute of Museum and Library Services’ Laura Bush 21st Century Librarian Program to the School of Information Sciences (SIS) at the University of Tennessee (UT). The purpose of both is to recruit and train rural library paraprofessionals working in the Southern and Central Appalachian (SCA) region to complete their master’s degree part-time in the UT SIS’ synchronous distance education program. Sixteen ITRL students completed their graduate education from June 2010 – August 2012 combining work experience in regional libraries with a curriculum that focused in information technology (IT) and rural librarianship, while thirteen ITRL2 students will complete a similarly structured program from June 2013 – August 2015. This paper discusses the social justice implications in its analysis of the recruitment methods in the ITRL and ITRL2 that have been made to identify the best candidates from the rural SCA communities.